Role of monocyte and lymphocyte counts in prognosis of cervical cancer - Jain, Aanchal; Bobdey, Saurabh; Sathwara, Jignasa; Ganesh, B.; Saoba, Sushma; Khan, Arshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Inflammation seems to play a very crucial role in the growth and progression of many cancers. It has been reported that a peripheral blood count has been used as a cost-effective and simple parameter of systemic inflammation in critically ill patients. The aim of this study is to investigate whether components of WBC counts can predict the prognosis of patients with cervical cancer. Methods: Medical records of 549 cervical cancer patients diagnosed between 1 January 2008 to 31 December 2008 were retrospectively analyzed. Receiver operating characteristic curve analysis and Cox proportional hazards model were applied to evaluate the effect of white blood cell (WBC) counts on overall survival. Results: The 5-year overall survival of the cohort was found to be 67.7%. On the basis of univariate analysis elevated monocyte count (≥0.515 109/L) and lower lymphocyte count (≤2.075 109/L) were associated with poor overall survival (OS) (p=0.016 and 0.002 respectively). Multivariate Cox proportional hazard analysis showed that higher monocyte and lower lymphocyte levels were a significant independent predictors for worse OS (HR = 1.555, 95% CI = 1.125-2.149; P=0.008) and (HR = 1.712, 95% CI = 1.232-2.379; P= 0.001) respectively. The advanced overall stage and treatment were also found to be independent indicators for poor OS. Conclusions: Pretreatment monocyte and lymphocyte count is an independent predictor of prognosis in cervical cancer patients. Thus it may be a cost effective marker to predict the outcome of cervical cancer patients.